Infusing economic characteristics into jewellery design process - Hashim, Hema Zulaika (2019)
Design is the ultimate creativity differentiator for a designer in producing much sought after jewellery creations in a highly competitive market. To achieve this, a designer should have a firm grasp concerning needs, science, technical knowledge, creativity, time frame and costing. With full understanding of the factors mentioned, the question hence emphasizes on if the design observes to the economics of production which in return provides added value to the customer. Therefore, a rigorous design process in an evolving economic consideration is crucial because a design process of an adornment should adhere to the acquiring capability of consumers’ reality. This study is aimed at developing a design process framework for jewellery designers as a guide to satisfying consumers’ needs. Focusing on jewellery design, the key objective of this research is classified under three domains; to identify the characteristics of jewellery products in relation to design and economics components, to formulate a design and economic framework model which act as functional guidelines for jewellery design industry and to integrate business thinking into jewellery design process. Designers are paving ways to deliver good designs which translates into tangible economic value to each customer. So, seen as a creative research, this study’s outcome from the framework developed are subjective and conceptual where mixed methods of qualitative and quantitative analysis are applied. This study was initiated with interviewed designers and jewellers and distributed the questionnaires to 120 respondents in view of practical outcome through the development of a DIAMOND matrix for Designomics framework based on the notion of design and economics integration in jewellery design. To realize the measurement of data in this research, the SPSS Software was used to measure Principle Component Analysis, descriptive analysis and hierarchical cluster analysis. The findings exhibited four main characters at the core of Designomics framework; Humanistic Value, Sentimentality, Economic Sustainability and Satisfaction Tolerance. The dissertation concludes with a discussion on the significance of jewellery designs with economic view that should influence Malaysia’s jewellery industry.